2020
DOI: 10.1590/0100-6991e-20202533
|View full text |Cite
|
Sign up to set email alerts
|

Trauma quality indicators: a way to identify attention points in the treatment of elderly trauma patients

Abstract: Purpose: to trauma quality indicators as a tool to identify opportunities of improvement in elderly trauma patient’s’ treatment. Methods: prospective analysis of data collected between 2014-2015, and stored in the iTreg software (by Ecossistemas). Trauma victims, aged older than 60 years and trauma quality indicators were assessed, based on those supported by SBAIT in 2013: (F1) Acute subdural hematoma drainage after 4 hours from admission, in patients with GCS<9; (F2) emergency room transference without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 15 publications
0
3
1
5
Order By: Relevance
“…Our findings are different from those found in previous studies related to the use of QIs in the identification of preventable complications and deaths 8 , 9 , whose results demonstrated improvement in the quality of care and in the outcome when the pre-established indicators were complied with. This difference suggests that pre-hospital care and surgical conduct strategies are the main factors related to mortality of patients with severe injuries 16 , 17 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings are different from those found in previous studies related to the use of QIs in the identification of preventable complications and deaths 8 , 9 , whose results demonstrated improvement in the quality of care and in the outcome when the pre-established indicators were complied with. This difference suggests that pre-hospital care and surgical conduct strategies are the main factors related to mortality of patients with severe injuries 16 , 17 .…”
Section: Discussioncontrasting
confidence: 99%
“…Several models of quality programs to trauma care have been proposed, such as morbidity and mortality meetings, study of avoidable deaths, auditing monitoring of indicators, establishment of morbidity and mortality review committees, cycle closing with the team, and especially trauma records. The use of trauma indices, such as the Glasgow Coma Scale (GCS) 5 , the Abbreviated Injury Scale (AIS) 6 and the Injury Severity Score (ISS) 7 to stratify the severity of the victims, associated with the monitoring of quality/auditing indicators (QIs), proved to be effective in identifying potentially preventable deaths 8 , allowing detailing of improvement points in care 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Early identification of trauma types and conditions and the formulation of corresponding treatment plans can improve the prognosis of patients and ensure the life and health of patients. Therefore, ensuring efficient first aid and improving the quality of nursing is the focus of clinical attention [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Efficient emergency treatment is a key factor in ensuring acute trauma patients. Previous studies have shown that every 3-minute delay in the effective treatment of acute trauma patients can increase the risk of death by 1% [ 12 ]. With the prolongation of injury time, a large amount of blood loss and fluid loss in acute trauma patients can not only lead to hypoxia but also increase the risk of ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…Os "filtros de auditoria" ou Filtros de Qualidade (FQ) são variáveis propostas pelos assistentes de cada serviço a serem monitoradas e que, quando presentes, podem representar oportunidades de melhora para o sistema [20][21][22][23][24][25] Além dos dados clínicos-demográficos, foi realizada a coleta de informações dirigida para avaliação de qualidade de atendimento, através de Filtros de Qualidade/ Auditoria, conforme aqueles já estabelecidos em nosso serviço 35,36 , baseados naqueles propostos inicialmente pelo American College of Surgeons em 199026 adaptando-nos o à realidade de nosso serviço e editando-os (Tabela 1). Houve 17 fraturas de ossos do crânio (3,65%), 21 fraturas de face (4,7%), 9 Hematomas Epidurais (2%), 8 Hematomas Subdurais (1,8%) e 12 contusões cerebrais (2,7%); 42 fraturas de membros superiores (9,1%), 50 de membros inferiores (10,8%) -com apenas 1 lesão vascular periférica -15 de pelve (3,2%) e 18 de coluna (3,9%).…”
Section: R E S U M O R E S U M Ounclassified